Design-for-comfort and fashion high-heel pump shoes for working women using melded QFD, TRIZ, and value engineering - Raneses, Nestor O.; Indardaya, Abdulah P.; Panabang, Maritess B.; Revil, Maria Socorro C.
While high-heel pump shoes are popular footwear among working women, they are also significant sources of discomfort, foot pains especially foot blisters. Using melded quality function deployment (QFD), TRIZ, and value engineering methods, the pump shoes were studied and re-designed for design-for fashion, fit, comfort and durability Results of the study and prototype indicated significant improvement in comfort and reduction in blisters and cost-effectiveness on the bill of materials and standard manufacture while maintaining design for fashion and styling.
Keywords: Design-for-fit and comfort high-heel pump shoes; Melded QFD; TRIZ; VE methods; Function cost analysis